Flint recycling in the Neolithic and Early Bronze Age: Evidence for small flakes production by means of recycling at Ein-Zippori, Israel. (2018) - Parush, Yoni; Yerkes, Richard W.; Efrati, Bar; Barkai, Ran; Gopher, Avi
No abstract available